PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPAS DI KELAS V SDN 060884 KECAMATAN MEDAN BARU TAHUN PEMBELAJARAN 2024/2025 - Zendrato, Agusman; Ambarwati, Nova Florentina; Tarigan, Paska Sriulina; Silaban, Patri Janson; Lumban Gaol, Rumiris (Jurnal Ilmiah Aquinas, 2025)
This study aims to determine the effect of the problem based learning model on students' critical thinking skills in the Science subject on the topic of My Region, My Pride, class V of Elementary School 060884, Medan Baru District, 2024/2025 Academic Year. The research method used is a quantitative method and the number of research samples is 30 based on the saturated sample technique. The results of this study indicate that the results of the critical thinking ability test with an average of 80. The results of this study indicate that the results of the correlation test r count 0.827 with a significance level of 5% with the number of respondents 30 so that r table 0.361. From these results it shows r count (0.827) > r table (0.361) then Ha is accepted. So there is a strong influence between the problem based learning model on the critical thinking skills of fifth grade students of Elementary School 060884 Medan Baru District. It can also be seen from the t-test where t count> t table is 7.787 > 1.701 so Ha is accepted. This shows a significant positive influence of the use of the problem-based learning model on the critical thinking skills of grade V students of Elementary School 060884, Medan Baru District, 2024/2025 Academic Year.